2014
DOI: 10.19030/iber.v13i6.8918
|View full text |Cite
|
Sign up to set email alerts
|

The Random Walk Theory And Stock Prices: Evidence From Johannesburg Stock Exchange

Abstract: In this paper, we test the Johannesburg Stock Exchange market for the existence of the random walk hypothesis using monthly time series of the All Share Index (ALSI) covering the period 2000 2011. Traditional methods, such as unit root tests and autocorrelation test, were employed first and they all confirmed that during the period under consideration, the JSE price index followed the random walk process. In addition, the ARIMA model was constructed and it was found that the ARIMA (1, 1, 1) was the model that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This makes the investors unable to get the abnormal returns in the financial market. A number of studies have supported the random walk theory/hypothesis like (Chitenderu, Maredza, & Sibanda, 2014;Marulkar & Faniband, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…This makes the investors unable to get the abnormal returns in the financial market. A number of studies have supported the random walk theory/hypothesis like (Chitenderu, Maredza, & Sibanda, 2014;Marulkar & Faniband, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…Therefore any attempt to forecast future stock prices will fail. Chitenderu et al (2014) are also of the view stock prices move in a random manner leading to the impossibility of forecasting stock prices in the market. Where there is an increase in stock price, an investor cannot foretell if there will be another increase as no correlation exists between past and future stock prices.…”
Section: Indicated Thementioning
confidence: 99%
“…This study revealed the fact that stock prices have a unit root that confirms the series is non-stationary and follows a random walk. In Africa, Chitenderu, Maredza, and Sibanda (2014) tested the existence of RWH in the All Shares index of the Johannesburg Stock Exchange. The period covered in the study was the year 2000 to 2011, and the outcome of the unit root test revealed that the data series was non-stationary and, therefore, followed a random walk.…”
Section: Finance Theoriesmentioning
confidence: 99%